Identification of a Disease on Cocoa Caused by Fusariumin Sulawesi - Ade Rosmana; Hikmawati Hikmawati; Asman Asman (Indonesian Coffee and Cocoa Research Institute, 2013)
A disease presumed to be caused by Fusarium was observed in cocoa open fields with few or without shade trees. Within the population of cocoa trees in the field, some trees had died, some had yellowing leaves and dieback, and the others were apparently healthy. In order to demonstrate Fusarium species as the causal pathogen and to obtain information concerning the incidence of the disease, its distribution and its impact on sustainability of cocoa, isolation of the pathogen, inoculation of cocoa seedlings with isolates and a survey of disease has been conducted. Fusarium was isolated from roots and branches, and inoculated onto cocoa seedlings (one month old) via soil. Symptoms appeared within 3-4 weeks after infection. These symptoms consisted of yellowing of leaves beginning from the bottom until the leaves falldown, and browning internal of vascular tissue. Darkened vascular traces in the petiole characteristic of vascularstreak dieback infection were absent. The occurrence of Fusarium in the field was characterized by the absence of obvious signs of fungal infestation on root of infected trees, yellowing of leaves on twigs, dieback, and tree mortality in severe infestations. Disease incidence could reach 77% and in this situation it was difficult for trees recover from heavy infections or to be regenerated in the farm. The study proves that Fusarium is a pathogen causing dieback and the disease is called as Fusarium vascular dieback (FVD). Its development is apparently enhanced by dry conditions in the field. Key words: Fusarium sp., vascular disease, dieback, FVD, Theobroma cacao L.